Postgraduate Students’ Realistic Mathematics Education (RME) Task Designs in Relation to Their Conceptual Knowledge - Rooselyna Ekawati; Novita Vindri Harini; Gurit Wulan Jagadianti; Mukhtamilatus Sa'diyah (Mathematics Education Journal, 2026)
This study examines postgraduate students’ Realistic Mathematics Education (RME) task designs in relation to their conceptual knowledge of RME principles and characteristics. A qualitative case study was conducted involving four postgraduate students in a Mathematics Education program selected purposively. Data were collected through two assignments: a conceptual diagnostic task requiring students to identify RME principles and characteristics within a given learning sequence, and a task design assignment requiring them to develop an RME-based worksheet. Document analysis was used to examine the relationship between students’ conceptual understanding and the alignment of their task designs with RME principles. The findings indicate that students with comprehensive conceptual knowledge produced task designs consistently aligned with RME principles and characteristics. However, classroom implementation revealed that theoretically well-aligned task designs did not always lead to successful student learning. This finding indicates a gap between task design and its enactment, highlighting the importance of task clarity and students’ interpretative processes in RME-based learning. Those with partial understanding demonstrated misplaced or incomplete learning stages, while students with limited conceptual knowledge generated designs lacking essential RME components. This study contributes to the RME literature by demonstrating how variations in conceptual integration are reflected in systematic misalignments in task design, providing implications for RME-oriented teacher education at the postgraduate level, aligned with SDG 4 on quality education.